El ontologismo en Augusto Del Noce - Lasa, Carlos Daniel (Sapientia, 2013)
From a revision of the concept of modernity (which, shaped by Enlightenment thinkers, strongly influenced part of the Catholic thought), Augusto Del Noce explores in the same modern time a Christian metaphysics school of thought called ontologist, which represents a continuity of the Christian metaphysical thought of St. Augustine as well as of St. Thomas Aquinas. Del Noce, as historian, values in a special way the instance of continuity, and it is from this idea, and not of the breakdown, which develops his own vision of modernity. The non-axiological approach, proper of the canonical and hegemonic version of the idea of modernity, will lead him to clarify the true nature of modern Christian ontologism. This, also, will allow him to lay down, from an inner dialectic between a rationalist and a religious version, the hermeneutic box in which he will place the historiographical reconstruction operated in Il problema dell’ateismo as well as in his following book Riforma cattolica e filosofia moderna.